The Role of Central Sharīʿah Advisory Board to Enhance Harmonization of Products and Services in Islamic Banking Institutions - Shahzad, Muhammad Asghar; Hassan, Shafiqul; Abbas, Hafiz Ghulam (Journal of Ecohumanism, 2024)
Islamic banking, firmly rooted in Sharīʿah principles, has emerged as a resilient alternative to conventional banking systems on a global scale. The adherence to Sharīʿah principles distinguishes Islamic banking from its conventional counterparts, shaping the ethos of its products and services. While various models of Sharīʿah supervision exist worldwide, Pakistan stands out with its adoption of a hybrid model blending centralized and decentralized approaches. This paper focuses on exploring the necessity and significance of a centralized Sharīʿah supervisory model through qualitative research methods. By delving into the unique features and challenges of centralized supervision, it provides valuable insights into strategies aimed at enhancing the efficacy of Central Sharīʿah Advisory Boards (CSABs). These strategies are pivotal in advancing the harmonization agenda within Islamic banking, reinforcing integrity, trust, and sustainability within the industry. Furthermore, the paper underscores the broader impact of CSABs on Islamic finance, emphasizing their role in promoting financial inclusion and socio-economic development not only in Muslim-majority countries but also beyond. By aligning banking practices with Sharīʿah principles and fostering transparency, CSABs contribute to a more equitable and resilient financial ecosystem, resonating with the core values of Islamic finance.